Devising a procedure for justifying the need for samples of weapons and weapon target assignment when using a reconnaissance firing system - Oleksandr Maistrenko (PC Technology Center, 2021)
This paper proposes an algorithm to substantiate the need for weapons samples, as well as targeting when using a reconnaissance firing system taking into consideration the peculiarities of functioning of such systems. The algorithm essentially implies streamlining the stages in determining the magnitude of the reduction of the enemy's combat potential and, on its basis, the formation of the need for the number of weapons by type. The algorithm makes it possible to take into consideration the nonlinearity of functions that describe both different types of weapons and targets. In addition, this algorithm is based on a modified method of nonlinear programming (two functions). The modification involves the use of a normalized share of the weight of each target as weight coefficients. This allows for targeting while taking into consideration the established level of the combat potential of an enemy.